Foreign satellite channels and their impact on the patterns of social values among Algerian university students - Berche, Bochra (Journal of Social Sciences and Humanities, 2023)
The era of modern communication technology has paved the way for new patterns of social life in many societies, and this is evident during the transition of television to the global circle due to the rapid development of satellite technology and modern communication technology, which led to the abolition of the monopoly of local television on viewers, and the end of the so-called media sovereignty. Or the control of the local media, as the channels, including foreign ones, have come to dominate the mass culture, because some media messages carry with them contents threatening the social values of the lives of many individuals as a result of the fascination and the spread of the phenomenon of imitation of Western lifestyles. On this basis, the study came to highlight the (negative and positive) effects that foreign satellite channels have had on the values of Algerian university students, by relying on a survey field study for a sample of Setif University students 2. The objectives of the study and the use of the questionnaire form as a main tool for obtaining information and unloading data. The theories of observational learning and uses and gratifications were relied upon as a guiding guide to explain the impact of foreign channels on the social values of Algerian university students. The study reached a set of results, which we summarize as follows: • The contents of foreign channels have left some negative effects associated with the values of students, and this is what emerges in preserving the traditions and customs of society, embodying social cooperation, and maintaining community security. • The female category is affected by the contents of Western satellite channels in more proportions than the males, and this is what is shown by the attached data in the table regarding the subtraction of the negative effects left by the contents of Western satellite channels on social values. • The contents of foreign channels leave some negative behaviors that primarily affect the social values of the male sample, and this is what lies in the feeling of emotional apathy within the social environment.